2022
DOI: 10.3390/ani12172234
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Changes of Heat-Treated Corn Grain Used in Ruminant Nutrition

Abstract: Cereal grain is processed using different combinations of heat, moisture, time, and mechanical action in order to improve its digestibility. The objective of the present research was to quantitatively represent the physicochemical properties of raw and processed starch using an in vitro methodology, as well as to describe the changes that occurred after heat treatment, such as pelleting, steam flaking, micronization, and extrusion of corn. Based on the obtained results, pelleting, steam flaking, and micronizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Wang et al [20] reported that the steaming of sorghum in the diet expanded total intake, which may have been caused by the greater palatability of feed containing steam and enhanced ruminal fermentation by increased ruminal digestible starch (RDS). Furthermore, this processing impact makes starch a more accessible surface for both ruminal microbial and pancreatic enzymes, which is beneficial to microorganisms in their proliferation and may contribute to digestion in the rumen [21]. The result of this study revealed an increase in CP nutrient intake when replacing 10 to 30% of CSC with WBTS, compared to the unsubstituted group (0% of WBTS), possibly because of the higher CP content in WBTS compared to CSC [4].…”
Section: Feeds Nutrient Intake and Digestibilitymentioning
confidence: 74%
See 2 more Smart Citations
“…Wang et al [20] reported that the steaming of sorghum in the diet expanded total intake, which may have been caused by the greater palatability of feed containing steam and enhanced ruminal fermentation by increased ruminal digestible starch (RDS). Furthermore, this processing impact makes starch a more accessible surface for both ruminal microbial and pancreatic enzymes, which is beneficial to microorganisms in their proliferation and may contribute to digestion in the rumen [21]. The result of this study revealed an increase in CP nutrient intake when replacing 10 to 30% of CSC with WBTS, compared to the unsubstituted group (0% of WBTS), possibly because of the higher CP content in WBTS compared to CSC [4].…”
Section: Feeds Nutrient Intake and Digestibilitymentioning
confidence: 74%
“…This occurs due to the hydrolysis or melting of some cellulose and hemicellulose components on the surface when materials are exposed to high temperatures [23]. Consequently, this process has the potential to alter and increase the specific surface area of the feedstuff, thereby enhancing feed utilization and digestibility [21,22,24]. Yahaghi et al [25] demonstrated that replacing barley with steam-treated sorghum grain in lamb diets could lead to improved ruminal fermentation and fiber digestibility.…”
Section: Feeds Nutrient Intake and Digestibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ljøkjel et al [22] found that heat treatment reduced the ruminal degradation of starch in both barley grain and pea grain. Srakaew et al [45] and Kokić et al [46] found that microorganisms have access to more starch in the rumen due to heat and moisture. The disorganization of the starch granules in the grain's endosperm and disruption of the protein matrix may be to blame for this problem.…”
Section: Microscopic Images Taken From Different Treatments At 48 H O...mentioning
confidence: 99%